Memoirs of the Life of Sir Walter Scott, Bart. - Lockhart, J. G. ([Verlag nicht ermittelbar], 1837)
As son-in-law and literary executor to Sir Walter Scott (1771–1832), John Gibson Lockhart (1794–1854) was uniquely placed to produce a definitive biography of the great poet and novelist. First published in 1837–8, shortly after Scott's death, this celebrated seven-volume work is based on personal memories, correspondence, and Scott's own autobiographical sketches. Wide-ranging in his purview, Lockhart is also detailed in his descriptions: the Aberdeen Journal of the day observed that the volumes trace Scott's life and literary efforts with 'the most minute distinctness'. Volume 6 covers the years 1825–6, during which Scott experienced literary triumph with the publication of Tales of the Crusaders (1825), continued to work on Woodstock (1826), and took an excursion to Ireland. The closing chapters cover the banking crises of 1825 and hint at the financial catastrophes that were to plague the author until his death seven years later.